Coleridge on the Language of Verse. - Marks, Emerson R. (Princeton University Press, 2017)
Drawing on the entire corpus of Coleridge's prose, Emerson Marks shows how the poet's rationale was grounded in the mimetic theory that informed his distinction between a copy and an imitation which Coleridge himself labeled the universal principle of the fine arts."Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Aesthetics.; Coleridge, Samuel Taylor, -- 1772-1834; Poetics -- History -- 19th century.; Poétique -- Histoire -- 19e siècle.; LITERARY CRITICISM -- Poetry.; Aesthetics; Poetics; 1800-1899; History